Characterizing mudstones and fault structure in Bumita Quarry, Perlis through integrated geophysical techniques - Mohd Muztaza, Nordiana; Hisham, Hazrul; Jia, Teoh Ying; Zakaria, Muhammad Taqiuddin; Ismail, Nur Azwin I; Md Dan M.F.M., Mohd Firdaus Md Dan @ Azlan; Adewumi, Taiwo (Geological Society of Malaysia, 2024)
The parameters of seismic refraction and electrical resistivity play a crucial role in geological studies, as they provide insights into the composition of rocks or soil beneath the Earth’s surface. Previous researchers have established reference ranges for seismic velocity and resistivity values based on different rock types, which are presented in tabulated forms. However, the wide variability in these values sometimes leads to challenges in interpretation due to overlapping ranges. In the region of Perlis, Malaysia, a comprehensive geophysical investigation involving seismic refraction and electrical resistivity methods was conducted within the Chepor Member of the Kubang Pasu Formation at the Bumita Quarry and Utan Aji. The results were then correlated with porosity and permeability data. The Chepor Member primarily comprises both red mudstone and grey mudstone. Interestingly, the seismic velocities of these two mudstone types are quite similar, differing only by a small margin of approximately 200 m/s. The resistivity method employed utilized a pole-dipole array configuration. In terms of resistivity values, the red mudstone exhibited lower readings (ranging from 15 to 100 Ωm) compared to the grey mudstone (ranging from 120 to 500 Ωm). Assessing porosity, the red mudstone displayed a value of 0.95%, alongside a permeability of 5.58x10-5 µd, while the grey mudstone indicated a slightly higher porosity value of 1.9% and a permeability of 2.06x10-5 µd. Consequently, the study successfully established seismic velocity and resistivity benchmarks for the mudstones within the Chepor Member geological unit.